Kanapoi revisited: Paleoecological and biogeographical inferences from the fossil fish. Issue 140 (March 2020) - Stewart, Kathlyn M.; Rufolo, Scott J.
Abstract: Fish fossils were recovered from three different depositional contexts at the Pliocene Kanapoi site to: 1) test the assumption that habitat and ecology of modern fish taxa can predict habitat and ecology of fossil taxa; 2) reconstruct the lake and river environments in the Kanapoi Formation, with reference to fish fossils from the nearby Lothagam site deposits; and 3) investigate biogeographical inferences from the fossils. We compare the Kanapoi fish taxa and their depositional environments with the taxa and environments in modern Lake Turkana, and with another Plio-Pleistocene fauna from the eastern Turkana Basin. Taphonomic caveats are discussed. Our results support the use of ecological preferences of modern fish to predict past preferences. Our analysis of the Kanapoi fossils also indicates that the Pliocene Lonyumun Lake had a diverse fauna, with an unusual mix of taxa compared to the modern lake. The presence of possibly endemic species in the Pliocene lake may additionally represent a period of isolation during this epoch. Few fish fossils were recovered in the deposits of the ancestral Kerio River, a primary affluent of Lonyumun Lake then as now, but those present indicate a different ecology than that interpreted for the modern lake. Previously unknown fish taxa which enter the lake during the Pliocene suggest the existence of a connection between the Nile River and the Turkana Basin, which may have been viable for other vertebrates, including hominins.